The Concept of Forming Shaleh Children According to Islamic Education - Risnawaty, Rattry (Lembaga KITA, 2023)
Children, viewed as a divine trust from Allah SWT, are entrusted to parents from the moment they grace the world. This bequeathed responsibility mandates parents to meticulously nurture and educate their progeny, directing them towards the cultivation of utility and noble character. Born in a state of fitrah, children's trajectories, whether towards virtue or peril, hinge significantly upon the guidance provided by parents. This responsibility extends beyond mere guidance; parents are entrusted with the monumental task of instilling piety in their children—a duty often underestimated by a substantial number of parents, despite explicit guidance in the Al-Qur'an and Hadith regarding the pivotal role of righteous offspring. This research, titled Concept of Forming Pious (Shaleh) Children According to Education, delves into this critical matter with precision. The research objectives encompass a nuanced understanding of the principles underpinning the cultivation of piety in children through education, exploration of methodologies employed in educating pious children, and identification of strategic efforts to foster piety from an educational standpoint. Employing a descriptive research methodology, the study undertakes a comprehensive examination of current issues through a thorough library research approach. The findings of this research underscore the imperative of cultivating pious children with the aim of nurturing individuals of noble character, thereby contributing to peace and tranquility in both temporal and spiritual realms. The practice of educating children in piety is characterized by its enduring nature, persisting beyond the corporeal realm, as the prayers of pious children become a poignant means of salvation for parents from the fires of hell upon their demise. The conceptualization of forming a pious child according to education involves the developmental nurturing of their soul, even within the confines of the womb, with the overarching goal of achieving virtuous outcomes. Efforts to foster pious children, from an educational perspective, entail the deliberate incorporation of moral education in both formal and informal educational settings. The methodologies employed in shaping pious children through education encompass exemplariness, adherence to cultural norms, the provision of advice, focused attention, and judicious application of appropriate disciplinary measures. In consideration of these insights, this research anticipates active parental engagement in cultivating their children's moral compass, fostering the nuanced development of pious offspring. Encouraging community participation in shaping the moral character of children towards piety is deemed essential. Furthermore, the sustained and active involvement of educators in schools, dedicated to imparting moral values, is paramount for the realization of a society characterized by pious children.